Analisa Probabilitas Perpindahan Moda Transportasi Dari Bus Ke Kereta Api Rute Medan-Kotapinang Menggunakan Metode Stated Preference - Artanto, Beni; Surbakti, Medis Sejahtera (Fakultas Teknik Universitas Katolik Santo Thomas, 2018)
The construction of railway line between Rantau Prapat and Kotapinang is expected to ease transportation process from Medan to Kotapinang, which could improve economic activities and become the alternative solution to make a trip. At the moment, existing public transport that covers this route is strictly limited to only medium or big buses. This research aims to identify the characteristic of trip maker and also to analyze the probability of mode shifting from bus to train for the mentioned trip. We use stated preference survey questionnaire, and it was distributed to random minimul sample needed. In order to obtain the utility function of the trip maker, the obtained data was then modeled in binomial logit method using SPSS statistical software. Tthe analyzed attributes difference (Δ) are trip cost difference (ΔX1), waiting time difference (ΔX2), travel time difference (ΔX3). The generated model has 0.114 of R2, and the probability of shifting from bus to train is 31.93% if the trip cost difference was Rp. 30.000. Meanwhile, the probability of shifting is 50.15% if the waiting time difference was less then 30 minutes. Lastly, the probability of shifting is 57.96% if the travel time difference was 1 hour.